DISASTER: a GIS database on hydro-geomorphologic disasters in Portugal - Zêzere, José (2014)
In the last century, Portugal was affected by several natural disasters of hydro-geomorphologic origin that often caused high levels of destruction. However, data on past events related to floods and landslides were scattered. The Disaster project aims to bridge the gap on the availability of a consistent and validated hydro-geomorphologic database for Portugal, by creating, disseminating and exploiting a GIS database on disastrous floods and landslides for the period 1865–2010, which is available in http://riskam.ul.pt/disaster/en. Data collection is steered by the concept of disaster used within the Disaster project. Therefore, any hydro-geomorphologic case is stored in the database if the occurrence led to casualties or injuries, and missing, evacuated or homeless people, independently of the number of people affected. The sources of information are 16 national, regional and local newspapers that implied the analysis of 145,344 individual newspapers. The hydro-geomorphologic occurrences were stored in a database containing two major parts: the characteristics of the hydro-geomorphologic case and the corresponding damages. In this work, the main results of the Disaster database are presented. A total of 1,621 disastrous floods and 281 disastrous landslides were recorded and registered in the database. These occurrences were responsible for 1,251 dead people. The obtained results do not support the existence of any exponential increase in events in time, thus contrasting with the picture provided to Portugal by the Emergency Events Database. Floods were more frequent during the period 1936–1967 and occurred mostly from November to February. Landslides were more frequent in the period 1947–1969 and occurred mostly from December to March.